Productive Or Life-Wasting : The Increasingly-Connected And Socially Networked Students - Curnow, Alexander; Kaur, Gursheena; Eban, Nomelyn; Kara, Esat; Mirlanov, Eldiiar (Universiti Malaysia Sarawak (UNIMAS), 2014)
The internet has only been with us since the 1980s (Leiner et al: 32) and public mobile phones for about 40 years (Smith 2009). In a single lifetime this is a ‘while’ but in terms of human history and in the longer-term scopes of social science this is a very short time. In the geological perspective of the age of the Earth, these technologies have been with us for less than a blink of an eye. This short time frame, no matter how many studies we have done and are doing on it, becomes crippling to social science study when it comes to proper perspective. Because we yet to empirically established an enduring conclusion on how the internet and other related modern gadgets are affecting us over our lifetimes. This is even more particular to the younger generation as most appeared to be hooked to these devices.